The role of key functions of shariah governance In Islamic Financial Institutions (IFIs) = دور الوظائف الأساسية للحوكمة الشرعية في المؤسسات المالية الإسلامية - Alnofli, Abdulrahman; Engku Ali, Engku Rabiah Adawiah (IIUM Press, International Islamic University Malaysia, 2020)
A solid governance in Islamic financial institutions (IFIs) is reflected in their efficient and sound operations. Due to the significant role of Sharī‘ah governance in enhancing and developing the operations and transactions of IFIs according to Sharī‘ah rules and principles, every IFI must have a sound Sharī‘ah governance framework. The key players of this governance should be defined and mentioned clearly. This paper discusses the role of key functions of Sharī‘ah governance in IFIs such as the Sharī‘ah Supervisory Board (SSB), Sharī‘ah review and Sharī‘ah audit. Moreover, this paper provides brief information about models of Sharī‘ah governance worldwide. The main objective of this study is to provide a clear insight about the key elements of Sharī‘ah governance in IFIs. In order to give this clear insight of the Sharī‘ah governance models, this study describes radically different models of Sharī‘ah governance, and focuses on their similarities and differences. ******************************************************************************** تعكس الحوكمة الشرعية الرشيدة في المؤسسات المالية الإسلامية في كفاءة وفعالية أنشطتها ومعاملاتها القائمة على هذه الحوكمة. ونظراللدور المهم للحوكمة الشرعية في تقوية وتطوير أنشطة المؤسسات المالية الإسلامية ومعاملاتها حسب أحكام الشريعة ومبادئها، لكل واحد ةمن هذه المؤسسات ينبغي أن يكون إطار سليم للحوكمة الشرعية، وكذلك لا بد من توصيف وتوضيح تلك الجهات التي يكون لها دور فعال في هذه الحوكمة. هذه الو رقة تناقش دور الوظائف المهمة والفاعلة لل حوكمة الشرعية في ا لمؤسسات المالية الإسلامية، منها الهيئة الشرعية والمراجعة الشرعية والتدقيق الشرعي .علاوة على ذلك ،هذه الدراسة تعطي رؤية شاملة لأنواع الحوكمة الشرعية السائدة في العالم، و تهدف إ لى إعطاء تصور واضح لأهم وظائف وواجبات الحوكمة الشرعية في المؤسسات المالية الإسلامية .ولإعطاء تصور واضح حول نماذج للحوكمة الشرعية، هذه الدراسة تبين أنواعا متعددة لهذه الحوكمة وتركز في بيان أوجه تشابهها وتباينه